Evaluation of the efficacy of carbon nanotubes for delivering peptides into mitochondria. Issue 71 (14th July 2016) - Ficociello, Graziella; Salemme, Adele; Uccelletti, Daniela; Fiorito, Silvana; Togna, Anna Rita; Vallan, Lorenzo; González-Domínguez, Jose M.; Da Ros, Tatiana; Francisci, Silvia; Montanari, Arianna
Abstract : Future therapy for mitochondrial pathologies: CKKSFLSPRTALINFLVK peptide from mitochondrial-LeuRS has a mitochondrial targeting activity when conjugated with multi-walled carbon nanotubes. Abstract : Mitochondrial (mt) diseases are devastating neurodegenerative pathologies due to mutations in nuclear or mt genes. Among mtDNA pathogenic mutations, more than one half have been identified in transfer RNA (tRNA) genes. These are responsible for a wide range of pathologies including myopathies, encephalopathies, cardiomyopathies and deafness for which no effective treatment is available at present. Therefore, new strategies to suppress their damaging effects are required to envisage therapeutic approaches for these diseases. Here we report data for carbon nanotube (CNT) derivatives showing that the conjugates bearing a specific peptide sequence are able to target the mitochondria in yeast and human monocyte cells while the control derivative without the peptide diffuses into the cytoplasm. Moreover the compounds do not affect cellular viability and cytotoxicity both in vitro and in vivo . Toxicity of the constructs is also assessed on the simple pluricellular model Caenorhabditis elegans .